An Error Analysis In Writing Short Essay Made By The First Semester Students English Department Nommensen University - Rosdiana Rajagukguk (LPPM Universitas HKBP Nommensen, 2023)
Writing is one of the learning topics taught at the Department of English Education at HKBP Nommensen University Medan. Meanwhile, based on the writer‟s experience the writer still made an error when writing an essay. The aims of this study are to find out the dominant types of error and the causes of the error. This study used qualitative descriptive as a case study. the population of this study was the 1sT semester students English Department of Nommensen University from groups A and B consist of 15 students. The data was collected from the students‟ tests and interviews. According to the result, there were four types of errors by using the appropriate tenses in writing a short essay made by the first semester students, those were (1). Omission (17.2%), (2). In Addition (10%), (3). Misformation (69.1%), and (4) Misordering (3.7%), the dominant types of error by using the appropriate tenses in writing a short essay made by the first semester students English Department Nommensen University on their short essay was Misformation (69.1%). The cause of the error by using the appropriate tenses in writing short essays was an Interlingual and Intralingual Transfer. this study indicates that there are still errors in writing short essays, which dominate by misformation errors or errors in word structure, which occurs because of interlingual and intralingual transfers or errors in the intended target language.